Healthcare Workers From Diverse Ethnicities and Their Perceptions of Risk and Experiences of Risk Management During the COVID-19 Pandemic: Qualitative Insights From the United Kingdom-REACH Study - Qureshi, Irtiza; Gogoi, Mayuri; Wobi, Fatimah; Chaloner, Jonathan; Al-Oraibi, Amani; Hassan, Osama; Pan, Daniel; Nellums, Laura B.; Pareek, Manish (Frontiers in Medicine, 2022)
Introduction Healthcare workers (HCWs) are at higher risk of being infected with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Previous studies have examined factors relating to infection amongst HCWs, including those from ethnic minority groups, but there is limited data regarding the lived experiences of HCWs in relation to self-protection and how they deal with SARS-CoV-2 infection prevention. In this study, we presented data from an ethnically diverse sample of HCWs in the United Kingdom (UK) to understand their perceptions of risks and experiences with risk management whilst working throughout the COVID-19 pandemic. Methods We undertook a qualitative study as part of the United Kingdom Research study into Ethnicity and COVID-19 outcomes among Healthcare workers (United Kingdom-REACH) conducting semi-structured interviews and focus groups which were recorded with participants’ permission. Recordings were transcribed and thematically analyzed. Findings A total of 84 participants were included in the analysis. Five broad themes emerged. First, ethnic minority HCWs spoke about specific risks and vulnerabilities they faced in relation to their ethnicity. Second, participants’ experience of risk assessments at work varied; some expressed satisfaction while many critiqued it as a “tick-box” exercise. Third, most participants shared about risks related to shortages, ambiguity in guidance, and inequitable distribution of Personal Protective Equipment (PPE), particularly during the start of the pandemic. Fourth, participants reported risks resulting from understaffing and inappropriate redeployment. Finally, HCWs shared the risk mitigation strategies which they had personally employed to protect themselves, their families, and the public. Conclusion Healthcare workers identified several areas where they felt at risk and/or had negative experiences of risk management during the pandemic. Our findings indicate that organizational shortcomings may have exposed some HCWs to greater risks of infection compared with others, thereby increasing their emotional and mental burden. Ethnic minority HCWs in particular experienced risks stemming from what they perceived to be institutional and structural racism, thus leading to a loss of trust in employers. These findings have significance in understanding staff safety, wellbeing, and workforce retention in multiethnic staff groups and also highlight the need for more robust, inclusive, and equitable approaches to protect HCWs going forward.